Safety and efficacy of pharmacologic weight loss in patients with cirrhosis - Ali Y. Fakhreddine; Samantha Bagsic; Ken Fujioka; Catherine T. Frenette (Wiley, 2021)
Abstract Background Obesity poses unique risks in patients with advanced liver fibrosis; however, given surgical risks of bariatric surgery in cirrhosis treatment recommendations are currently limited to lifestyle interventions. This study seeks to inform a potential treatment gap by describing the safety and efficacy of pharmacologic weight loss in patients with advanced liver disease. Methods A retrospective chart review of the electronic medical record was conducted for all patients in the Scripps Health system from 2005 to 2017 with established advanced liver fibrosis that were prescribed medications associated with weight loss. The primary outcome was safety as defined by the model for end‐stage liver disease (MELD) score. Secondary outcomes included total body weight loss, reasons for medication discontinuation, medication adverse events, and hospitalization before and after medication initiation. Results Thirty‐eight patients and 63 prescriptions were included in the final analysis. The most frequently prescribed medication associated with weight loss was metformin (63%, n = 24) followed by a GLP‐1 agonist (39%, n = 15). There was no significant effect of weight‐loss medication on MELD score (p > 0.18) or number of hospitalizations when adjusting for subject (p > 0.26). There was a significant adjusted mean weight loss of 2.2 kg (p < 0.02) following prescription of a medication associated with weight loss. The Federal Drug Administration‐approved anti‐obesity medications as a group resulted in a significant adjusted weight loss of 7.22 kg (p < 0.013). In a linear mixed‐effects model accounting for subjects, weight loss was not independently associated with a change in MELD (t[51] = −1.972, p > 0.05). Conclusion Pharmacologic weight loss in patients with advanced liver fibrosis appears feasible based on preliminary safety and efficacy outcomes in this study. Future prospective studies are warranted to evaluate a potential significant treatment gap in the management of obesity in this vulnerable population.